Electrochemical Immunosensor Platform Using Low-Cost ENIG PCB Finish Electrodes: Application for SARS-CoV-2 Spike Protein Sensing - Ruchira Nandeshwar (IEEE, 2021)
In recent years, lab-on-chip systems based on printed circuit board (PCB) substrates are gaining attraction primarily due to their low cost of manufacturing. Adapting inexpensive PCBs for development of immunosensors usually requires additional processing steps such as gold electroplating and electropolymerisation, that add to the manufacturing costs. In this work, we demonstrate methods to leverage electroless nickel immersion gold (ENIG) finish PCBs as electrodes for developing electrochemical immunosensors. We evaluated the performance of various parameters that impact sensor performance such as methods to clean impurities on PCB surface, optimization of redox probe concentration, and have successfully immobilized antibodies on the electrodes with cysteamine + glutaraldehyde aided process. Based on these methods, we demonstrate an application of ENIG finish PCB electrodes for detection of SARS-CoV-2 spike protein spiked in artificial saliva samples.